(3JGL GddZI hUMGM GdYQHjIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s ((3eMeO Hf bGSe Hf SYO Hf MSjf GdSHGYi GdUfYGfi s)
(3ChdgG (B:s
(3jHJOF HHGH GdPGd (B_ (3aUd GdCda c CNPJ GdTF CNPg CNPkG JfGhdJg s
(3BNQgG (B:s
(3BNQg ef HGH GdbGa , aUd GdSjf , eGOI Sgb bhdg (B: (3GdSghb GdWhjd ef GdQLGd , hGdTOjO ef GdQjGM Yf GdaQGA Je GdLRA s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf hCSeGA GdCHhGH hGdaUhd hGdehGO HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
Keywords: (3GddZIs